2016
DOI: 10.1159/000441917
|View full text |Cite
|
Sign up to set email alerts
|

Low Serum Vitamin D Levels May Contribute to Gastric Dysmotility in de novo Parkinson's Disease

Abstract: Background and Objectives: Gastrointestinal dysfunction is a common non motor symptom in Parkinson's disease (PD). However, the potential association between vitamin D and gastroparesis in PD has not been previously investigated. The aim of this study was to compare vitamin D levels between drug-naive de novo PD patients with normal gastric emptying and those with delayed gastric emptying. Methods: Fifty-one patients with drug-naive de novo PD and 20 age-matched healthy controls were enrolled in this study. Ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…According to the Braak model of neuropathological staging of PD, the early stages 1 and 2 start from the medulla and the olfactory bulb [112], supporting a relationship between vitamin D and early PD. In addition to being associated with dementia and olfactory function in PD patients, serum 25(OH)D 3 concentrations can also affect the gastric emptying time [113] and orthostatic hypotension [114].…”
Section: The Relationship Between Vitamin D Level and Clinical Manifementioning
confidence: 99%
“…According to the Braak model of neuropathological staging of PD, the early stages 1 and 2 start from the medulla and the olfactory bulb [112], supporting a relationship between vitamin D and early PD. In addition to being associated with dementia and olfactory function in PD patients, serum 25(OH)D 3 concentrations can also affect the gastric emptying time [113] and orthostatic hypotension [114].…”
Section: The Relationship Between Vitamin D Level and Clinical Manifementioning
confidence: 99%
“…[ 15 ] Low serum 25(OH)D levels are associated with delayed gastric emptying time (GET) assessed by scintigraphy in Parkinson's disease patients that were divided into a delayed-GET group and a normal-GET group. [ 16 ]…”
Section: Itamin D For G mentioning
confidence: 99%
“…Epidemiological investigations have suggested that serum 25-hydroxyvitamin D (25(OH)D) level has significantly inverse associations with various neurological and neurodegenerative diseases [1823]. However, little is known about 25(OH)D level in human cerebrospinal fluid (CSF).…”
Section: Introductionmentioning
confidence: 99%